Perancangan Sistem Informasi Sekolah Berbasis Web pada SMPT Darussalam Reni Jaya - Jagad Putra Natarendra; Sadam Sofyan; Nabil Radina; Maulana Ardhiansyah (CV. Multi Kreasi Media, 2026)
SMPT Darussalam Reni Jaya is a junior high educational institution that integrates Islamic values with digital technology developments. However, the dissemination of school information to the public is still conducted conventionally through notice boards and printed brochures, resulting in limited reach and a lack of accessibility anytime and anywhere. This condition leads to unstructured storage of teacher data and activity documentation, as well as minimal information received by prospective new students and parents, particularly during the New Student Admission (PPDB) period. This study aims to design and develop a Web-Based School Information System at SMPT Darussalam Reni Jaya using the PHP programming language and MySQL database with the Waterfall method. The resulting system includes features for managing school profiles, teacher data, news, activity galleries, and flagship programs, which can be managed by an administrator through a dashboard without altering the program code. The results of black box testing indicate that all system functions operate according to the design.